In bed with Wall Street : the conspiracy crippling our global economy - Doyle, Larry, 1960- (Palgrave Macmillan, 2014)
The Wall Street meltdown in 2008 brought the country to its knees and spawned nationwide protests against the lack of regulation and oversight in the financial industry. But the average American still fails to fully grasp what was--and still is--happening: that the inmates run the asylum. Larry Doyle exposes how financial executives, politicians, and even the regulators charged with overseeing the banks have conspired for personal gains while deceiving largely unprotected investors, consumers, and American taxpayers. He details the shocking corruption of the SEC, FINRA, and other "financial police," painting them as meter maids who assess nominal fines and look the other way at even the most egregious abuses. Most importantly, he unveils the revolving door of Wall Street, where countless regulators (and plenty of legislators) are former or future employees of the very firms they're tasked with overseeing. Recent bombshells--such as multi-billion dollar trading losses at JP Morgan Chase, the manipulation of interest rates via the LIBOR scandal, and money laundering with North American drug cartels and rogue nations such as Iran--are symptomatic of this corrosive culture, which has decimated consumer and investor confidence. As the big banks fight tooth and nail to avoid real reforms, this book is a timely, important, and shocking look at a hopelessly compromised system, still defenseless against the next great crash.--From publisher description.